2015
DOI: 10.1002/ente.201500175
|View full text |Cite
|
Sign up to set email alerts
|

How to Overcome the Water–Gas‐Shift Equilibrium using a Conventional Nickel Reformer Catalyst

Abstract: The catalytic water–gas‐shift (WGS) reaction into hydrogen and carbon dioxide was investigated using a commercial nickel reformer catalyst. The effects of temperature, flow rate, and catalyst nature on the course of reaction were evaluated. Hydrogen and carbon dioxide were generated in the temperature range between 125 and 475 °C. A reaction scheme was used to explain the formation of methane. The WGS reaction and the methanation reaction (MTN) were used to calculate the equilibrium composition at these condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The most obvious explanation is the fact that BRM is an endothermic and volume increase reaction, meaning that the conversion of all the reactants involved an increase in temperature with higher inert gas ow rates, as thermodynamically proven in a previous study. 59 Considering the side reaction scheme proposed in our previous works, 9,10 in particular CMD, SRM and DRM, the results obtained from the thermodynamic equilibrium calculations for inert gas variations are effectively clear. The exception is the single WGS reaction equilibrium, also a possible side-reaction, is not affected by the total pressure or partial pressure of inert gas.…”
Section: Catalytic Performancementioning
confidence: 91%
See 1 more Smart Citation
“…The most obvious explanation is the fact that BRM is an endothermic and volume increase reaction, meaning that the conversion of all the reactants involved an increase in temperature with higher inert gas ow rates, as thermodynamically proven in a previous study. 59 Considering the side reaction scheme proposed in our previous works, 9,10 in particular CMD, SRM and DRM, the results obtained from the thermodynamic equilibrium calculations for inert gas variations are effectively clear. The exception is the single WGS reaction equilibrium, also a possible side-reaction, is not affected by the total pressure or partial pressure of inert gas.…”
Section: Catalytic Performancementioning
confidence: 91%
“…The exception is the single WGS reaction equilibrium, also a possible side-reaction, is not affected by the total pressure or partial pressure of inert gas. 59 The material selected as a support for the promoter and active phase, LDH, as shown in Fig. 5, exhibited poor catalytic activity at low temperatures and reasonable catalytic activity at very high temperatures of around 850 C and higher.…”
Section: Catalytic Performancementioning
confidence: 99%
“…The temperature range achieved in the lower part of the packed bed shows that both catalytic reforming and CO 2 adsorption over zeolite are suitable in the operating conditions that were achieved. According to Cunha et al [61], water conversion into hydrogen through steam gasification reactions start being verified at around 120 • C with nickel-based catalysts, even if full conversion would require temperatures in the range of 200 • C. Moreover, CO 2 adsorption over zeolite has also been reported at atmospheric pressure levels and temperature ranges around 100 • C. Zhao et al [3], for instance, reported that zeolite can adsorb CO 2 over its surface with efficiencies above 5% under relatively low pressure and temperature levels. Considering such reported records together with the temperature registers, it is possible to affirm that the packed bed has activity in the syngas quality obtained from the gasifier.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the methanation of CO x (x = 1o r2 )a nd H 2 [Eqs. (3) and (4)], which are exothermic reactions.W ith decreasing temperature,C H 4 is produced from C 2 H 6 and C 3 H 8 faster than it is decomposed, which results in af ast increase in the selectivity to CH 4 .T his is probably due to the low reactivityofm ethane at lower temperature.…”
Section: Optimization Of Nickel Loadingmentioning
confidence: 99%
“…This providess everal benefits, including ad ecrease in potential carbon depositions in the tubularr eformer, increased feed flexibility,a nd reduced energy consumption. [2] Thea diabatic prereformingp rocess is based on as et of reactions: [3,4] steam reforming of hydrocarbons (1), followed by the watergas shift reaction (2), and methanation of CO x (3 and 4).…”
Section: Introductionmentioning
confidence: 99%